HUBUNGAN ANTARA KELEKATAN ANAK PADA IBU DENGAN KEMAMPUAN SOSIALISASI ANAK USIA 4-5 TAHUN (STUDI PADA RA SINAR PELANGI DAN RA AL IMAN KECAMATAN GUNUNGPATI, SEMARANG) - Anapratiwi, Devi (BELIA: Early Childhood Education Papers, 2013)
Social skill is a willingness to learn the standards, values??, and behavior expected for a particular culture or society. Attachment formed between children in mothers affects their social skills. Children attachment in mothers is also associated with social behavior of them later in life. Difficulty in socializing will greatly influence the children so that it will hamper them to achieve success in the future. The purpose of this study was to determine whether there is a relationship between maternal attachments to the children's social skills in children aged 4-5 years. This study used correlational approach, which involved 50 children, 4-5 years old, at RA Sinar Pelangi and RA Al Iman Gunungpati district. The data was collected by using questionnaires. Based on the analysis of the regression calculation results, researcher obtained significance of 0.000 less than p = 0.05 and t = 10.363 which showed positive relationship between secure attachment in mothers with children social skills. In anxious attachment, researcher obtained significance of 0.002 less than p = 0.05 and t = -3.209 which showed negative relationship between anxious attachment in mothers with children social skills, and researcher also obtained significance of 0.000 less than p = 0.05 and t = -7.226 in rejection attachment which showed negative relationship between rejection attachment in mothers with children social skills. It can be concluded that there is a relationship between 4-5 years children attachment in mothers with their social skills in RA Sinar Pelangi and RA Al Iman Gunungpati District, Semarang. For parents, especially mothers, as the people who are closest to the child's mother is expected to provide a consistent and responsive care that secure attachment is formed so that someday may form children who has good social skills because social skills will greatly influence the children to achieve success in the future.